Research Study on the Development of PJBL Teaching Modules Integrated with Augmented Reality to Increase Activity and Learning Outcomes of Grade V Students - Narpiyanto, Narpiyanto; Subali, Bambang; Widiarti, Nuni; Yuwono, Agus (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2025)
This study examines the development of project-based learning (PJBL) modules integrated with Augmented Reality (AR) technology for solar system material for grade V elementary school students. The main objective of the research is to improve learning activities and student learning outcomes through a more interactive learning experience and real visualization. The methodology used is a systematic literature review (SLR) to collect and evaluate related research from various sources from 2015 to 2025. The results show that the application of AR in learning modules can increase motivation, student engagement, and understanding of abstract astronomy concepts. However, there are challenges related to infrastructure and user training that need to be addressed for optimal implementation. The findings support the development of innovation in basic education through the effective and practical use of AR technology.